Optimizing prospective teachers’ representational abilities through didactical design-based lesson study - Isnawan, Muhamad Galang; Alsulami, Naif Mastoor; Sudirman, Sudirman (Institute of Advanced Engineering and Science, 2024)
This research aimed to optimize the representational abilities of prospective mathematics teachers through the implementation of hypothetical lecture designs. The research design used was didactical design research combined with lesson study activities. Participants in this research were 29 prospective mathematics teacher students (18–21 years old) at a private university in Mataram, Indonesia. The researcher was the main instrument, with several additional instruments, one of which was the hypothetical lecture design. After conducting qualitative data analysis, it was concluded that there was an increase in the percentage of students’ representation abilities through the implementation of hypothetical lecture designs. This was because the course design facilitated students to solve problems by exploring, using, and presenting ideas in various forms of representation. Apart from that, the lecture design integrated QR codes, Quizizz, and inspirational YouTube videos to attract students’ interest or motivation during lectures, especially when solving problems.